2022
DOI: 10.3390/su14148675
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Agricultural Machinery Using Multi-Criteria Analysis Methods

Abstract: To achieve the highest possible agricultural production, it is necessary to procure the appropriate agricultural machinery. A tractor is the most useful machine in agriculture that performs various functions. Therefore, the selection of a tractor is one of the key decisions in the agriculture-production process. This study aims to evaluate heavy tractors for agricultural production in Bosnia and Herzegovina. Since this is a selection between different tractors, which are evaluated using several criteria, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…Given the limited scale of their agricultural operations, these households frequently opt to invest in a compact tractor to augment their capabilities. A tractor, as established by Puška et al (2022), stands as the cornerstone of agricultural machinery. Consequently, it is unsurprising that the predominant choice in machinery procurement is the acquisition of a tractor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the limited scale of their agricultural operations, these households frequently opt to invest in a compact tractor to augment their capabilities. A tractor, as established by Puška et al (2022), stands as the cornerstone of agricultural machinery. Consequently, it is unsurprising that the predominant choice in machinery procurement is the acquisition of a tractor.…”
Section: Methodsmentioning
confidence: 99%
“…Their research not only demonstrated the importance of considering sustainability but also offered insights for the local brand production to meet the demands of international markets. Puška et al (2022) directed their attention to heavy tractors in Bosnia and Herzegovina (BiH), recognizing the need for efficient agricultural production. They utilized five methods to determine the criteria weights, introducing a novel one named the modified standard deviation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Application field 1 Krishankumar and Ecer (2023) IoT service provider selection 2 Wang et al (2023) Occupational risk assessment 3 Puška et al (2022a) Waste incinerator selection 4 Puška et al (2022b) Pear varieties market assessment 5 Puška et al (2022c) Green supplier selection 6 Starčević et al (2022) Foreign direct investment impact assessment 7 Wątróbski et al (2022) Extension of two developed Python packages 8 Puška et al (2022) Agricultural machinery assessment 9 Dordevic et al (2022) Production optimization 10 Stojanović et al (2022) Global Innovation Index analysis Source: Author's research…”
Section: Authorsmentioning
confidence: 99%
“…У овом раду предложена је примена једноставног објек-тивног модела заснованог на методама вишекритеријумског одлучивања који може помоћи у проналажењу оптималног LMS система погодног за примену у образовним институцијама. Предложени модел заснива се на објективној методи за дефинисање тежина критеријума под називом MEREC (MEthod based on the Removal Effects of Criteria) (Keshavarz-Ghorabaee et al, 2021) и недавно предложеној CRADIS методи (Compromise Ranking of Alternatives from Distance to Ideal Solution) (Puška et al, 2022), која је искоришћена за коначну оцену алтернативних LMS система. Шест алтернативних LMS система подвргнуто је евалуацији у односу на шест критеријума, а у сам процес била су укључена три стручњака из области информационих технологија који се непосредно баве учењем на даљину.…”
Section: оцена система за управљање учењем заснована на методама више...unclassified
See 1 more Smart Citation